A continental scale trophic cascade from wolves through coyotes to foxes. (9th July 2014) - Newsome, Thomas M.; Ripple, William J.; Coulson, Tim
Summary Top‐down processes, via the direct and indirect effects of interspecific competitive killing (no consumption of the kill) or intraguild predation (consumption of the kill), can potentially influence the spatial distribution of terrestrial predators, but few studies have demonstrated the phenomenon at a continental scale. For example, in North America, grey wolves Canis lupus are known to kill coyotes Canis latrans, and coyotes, in turn, may kill foxes Vulpes spp., but the spatial effects of these competitive interactions at large scales are unknown. Here, we analyse fur return data across eight jurisdictions in North America to test whether the presence or absence of wolves has caused a continent‐wide shift in coyote and red fox Vulpes vulpes density. Our results support the existence of a continental scale cascade whereby coyotes outnumber red foxes in areas where wolves have been extirpated by humans, whereas red foxes outnumber coyotes in areas where wolves are present. However, for a distance of up to 200 km on the edge of wolf distribution, there is a transition zone where the effects of top‐down control are weakened, possibly due to the rapid dispersal and reinvasion capabilities of coyotes into areas where wolves are sporadically distributed or at low densities. Our results have implications for understanding how the restoration of wolf populations across North America could potentially affect co‐occurring predators and prey. We conclude that large carnivores may need to occupy large continuous areas to facilitate among‐carnivore cascades and that studies of small areas may not be indicative of the effects of top‐down mesopredator control.